PERUMPAMAAN “NYAMUK” DI DALAM AL-QUR’AN : (KAJIAN ASBAB AL-NUZUL SURAH AL-BAQARAH AYAT 26) - Ahmad Agus Salim (Jurnal Asy-Syukriyyah, 2022)
The verses in the Qur'an are categorized into two types: first, the verses that were revealed as guidance and guidance for humans without being preceded by certain causes, and second, the verses that were revealed in response to events and reality. what happened in the community where the Qur'an was revealed. Although in quantity, fewer verses of the Qur'an were revealed due to certain reasons, but the scholars paid special attention to these verses through a discussion of the reasons for the revelation of the verses of the Qur'an or commonly known as the Qur'anic verses. Asbab al-Nuzul science. The results obtained in this article are first, because the revelation of verse 26 is due to the denial of unbelievers and hypocrites to the parables made by Allah SWT for them in surah al-Baqarah verses 17 and 19. Second, the content of the interpretation in the verse 26 in Surah al-Baqarah which explains the purpose of Allah's parable in the verse, also explains the nature of the characteristics of believing Muslims and the nature of hypocrites, and explains the recompense for the fasiq who Allah has misguided with his parables. . Third, the interpretation of verse 26 in surah al-Baqarah because al-Nuzul is two interrelated elements (relevant), which is a rebuttal verse against the denial of hypocrites to the parable made by Allah SWT, and the parable is in line with the meaning His word is that he does not hesitate to use it (mosquito) as an example.